A case of gingival stem cell administration using adipose tissue-derived stem cells - Yukako Suzuki (Wolters Kluwer Medknow Publications, 2020)
Adipose tissue-derived stem cells (ASCs) are reported to be capable of differentiating into all of mature cells, including bones and cartilage as same as bone marrow mesenchymal stem cells. In this study, we examined to treat periodontal disease using autologous ASCs to avoid rejection by transplantation. After autologous ASCs were injected into the gingiva, X-ray examination, periodontal pocket examination, and bleeding on probing were good results, and we obtained regeneration of periodontal tissue. Autologous ASCs are also easy to collect. Compared with other periodontal regeneration treatments, the burden on patients with less risk of postoperative infection is also less. In future, we hope to consider combined use with growth factors to aim at the alveolar bone and periodontal tissues regeneration. Moreover, we hope to conduct further investigations with a large number of cases over a long period of time.